1988
DOI: 10.1172/jci113645
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration by in situ hybridization of the zonal modulation of rat liver cytochrome P-450b and P-450e gene expression after phenobarbital.

Abstract: The various physiological processes that constitute liver function are compartmentalized within the hepatic acinus. The molecular mechanisms modulating the development and maintenance of this hepatocyte heterogeneity have not been defined. The objective of this study was to determine whether transcriptional or posttranscriptional zonal modulation of cytochromes P450b,e gene expression was responsible for the heterogeneous induction of the P450 proteins, which is observed after phenobarbital (PB) administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
3
13
0
Order By: Relevance
“…The regulatory level of this zonal differentiation in constitutive and induced expression of P450 genes is poorly understood. It has been shown that the acinar distribution of mRNA and protein for CYP2B1/2 is similar [28] and that also induction by acetone and phenobarbital, which is known to be transcriptionally regulated [14] is similarly located at the mRNA and protein level [28]. A congruent localisation of CYP2E1 mRNA and protein is also observed [lo, 291 and recent evidence suggests that this is due to higher rate of CYP2EI gene expression in nuclei from perivenous as compared to periportal hepatocytes [29].…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory level of this zonal differentiation in constitutive and induced expression of P450 genes is poorly understood. It has been shown that the acinar distribution of mRNA and protein for CYP2B1/2 is similar [28] and that also induction by acetone and phenobarbital, which is known to be transcriptionally regulated [14] is similarly located at the mRNA and protein level [28]. A congruent localisation of CYP2E1 mRNA and protein is also observed [lo, 291 and recent evidence suggests that this is due to higher rate of CYP2EI gene expression in nuclei from perivenous as compared to periportal hepatocytes [29].…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen tension in the PP zone is 60–65 mmHg and in the PV zone is 30–35 mm Hg 126–128 . These gradients, along with differences in ECM composition, structure, and soluble factors from the PP to PV zones 74 manifest as differences in cellular metabolism, including that of xenobiotics and secreted molecules, as well as changes in the morphology and number and phenotypic characteristics of all cell types along the PP-PV axis 128–130 (see Fig. 2).…”
Section: Livermentioning
confidence: 99%
“…1975) and immunocytochemistry of peroxisomal enzymes (Fahimi and Baumgart, 1993). as well as for in situ hybridization (Saber et al, 1990; Wojcik et al, 1988;Tournier et al, 1987). The initial rinsing of the liver with saline removes the blood components from the vascular spaces, exposing the hepatocytes directly to the fixative and preventing the loss of mRNA.…”
Section: Perfusion -Fiution Of the Livermentioning
confidence: 99%